Twenty-First Century Instructional Design: Guiding Vocational Instructors Designing E-Module - Nugroho, Windiyati; ,, Mustaji; Arianto, Fajar (Journal of Technical Education and Training, 2023)
Instructional design can be challenging in a vocational education setting, such as in a beauty institution where knowledge has to be balanced with practice, and trained individuals in this area are needed specifically for the new and emerging profession of health and beauty consultant. The e-module was designed using the Dick and Carey model consist of 10 steps. This study uses qualitative approach through semi-structured interviews conducted online with 3 students, 1 instructor and 2 observers from skin analysis class in PIBI Surabaya. The transcribed interview data were analysed using Atlas.ti software to produce codes.This study aimed to develop an instructional design for non-formal vocational education as a guide for instructors in creating quality training using an online learning approach. Based on the qualitative results, there are 4 categories that the researcher were asking about, which is media, content, strategy, and student’s response with feasible, practical and effective as the indicators. This study concluded that the instructional design can be used as a reference for instructors in preparing and delivering learning materials where the focus is centred on individual student, with the end goal of achieving competencies (attitude, skill and knowledge/ASK), eight employability skills, five dimensions of competence and twenty-first century skills according to the needs of the industry nowadays.